Effect of vacuum packaging on the shelflife of chilled, pre-cooked bagnet - Mercado, Arvin R.; Francisco, Ma. Leonora dL. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
Bagnet is a native Filipino dish made from fried and salted pork belly. This dish originated in Ilocos but variations from different parts of the archipelago is available. In this study, the effect of vacuum packaging on the microbial and sensory properties of chilled, pre-cooked Bagnet was determined. Aerobic-packed (AP) Bagnet samples served as control. The Total Plate Count (TPC) of vacuum-packed (VP) Bagnet samples was observed to be lower than the control throughout storage time at low temperature. Vacuum-packed samples were within the acceptable microbial limit until day 8, as compared to the control (day 2). Staphylococcal counts for both samples exceeded the standard, including count from day 0 while Lactic Acid Bacteria (LAB) were not inhibited by vacuum packaging. The high microbial load of chilled, pre-cooked Bagnet samples may be due to post-contamination, especially after baking and before vacuum packaging. Minimal changes in the overall acceptability as well as acceptance of color, aroma, flavor and texture were observed across storage time for both samples. At day 10, all samples had an average Hedonic rating of 5, equivalent to ?neither like nor dislike?. A significant difference in terms of intensity of saltiness was observed between replicates though. Product standardization as well as implementation of good manufacturing practices and Hazard Analysis and Critical Control Points is suggested to maintain the quality and safety of chilled, pre-cooked Bagnet.
Thesis (B.S. Food Technology)-University of the Philippines Diliman
Keywords: Food -- Packaging -- Philippines; Bagnet